Testing Data Security Using a Vigenere Cipher Based on the QR Code - Rachmawanto, Eko Hari; Gumelar, Rizky Syah; Nabila, Qotrunnada; Sari, Christy Atika; Ali, Rabei Raad (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
Data, especially personal data, is sensitive and if misused, it can become a source of threats and crimes for ourselves or for others. Therefore, data security is very important. Cryptography is a way to secure data that aims to safeguard the information that contained in data, so the information contained is not known by unauthorized parties. Vigenere Cipher is a cryptographic method used to hide data with steganography. In the process, the Vigenere cipher converts information called plain text into ciphertext or text that has been steganographed. In this research, process of encryption was carried out on the text based on the given key. The results of the text encryption were stored in the form of a QR-Code which can later be decrypted from the QR-Code using the key, so that the text contained in the QR-Code can be identified.